2005
DOI: 10.1186/1471-2253-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia in a surgical intensive care unit

Abstract: Background: Inadvertent hypothermia is not uncommon in the immediate postoperative period and it is associated with impairment and abnormalities in various organs and systems that can lead to adverse outcomes. The aim of this study was to estimate the prevalence, the predictive factors and outcome of core hypothermia on admission to a surgical ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
5
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 59 publications
4
67
5
15
Order By: Relevance
“…Hypothermia is thought to be a common and important physiological abnormality in surgical patients admitted to intensive care units (ICUs). Previous studies of postoperative hypothermia in ICU patients have used a single temperature observation (often on admission) and examined small patient groups, usually from one centre [1][2][3][4][5][6]. Despite these limitations, in studies of heterogeneous cohorts of postoperative patients, hypothermia was independently associated with complications and increased mortality [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia is thought to be a common and important physiological abnormality in surgical patients admitted to intensive care units (ICUs). Previous studies of postoperative hypothermia in ICU patients have used a single temperature observation (often on admission) and examined small patient groups, usually from one centre [1][2][3][4][5][6]. Despite these limitations, in studies of heterogeneous cohorts of postoperative patients, hypothermia was independently associated with complications and increased mortality [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 43.8% of the patients (n=81) were heated perioperatively. Hypothermia was observed in 55 of the heated patients [11]. It has been observed in our study that 7 patients received perioperative heating and none of them had postoperative hypothermia.…”
Section: Discussionmentioning
confidence: 74%
“…In the postoperative period, in 7,9% of the patients (13/165) hypothermia was detected; and deep hypothermia was detected in 1,8% (3/165) of them. In similar studies, it was reported that postoperative hypothermia was observed at much higher temperatures [10][11][12].…”
Section: Discussionmentioning
confidence: 76%
“…Several authors found high incidences of hypothermia ( < 36 ° C) ranging from 41 % to more than 60 % in postoperative surgical patients on arrival in the intensive care unit (ICU) [1,58,59,93] .…”
Section: Incidence Of Perioperative Hypothermiamentioning
confidence: 99%